Scaling relative incentive value: Different adjustments to incentive downshift in pigeons and rats - Pellegrini, Santiago (2008)
Previous research suggests that pigeons and rats show differences in their behavioral adjustments in spaced-trial, incentive-downshift situations. Also, Papini and Pellegrini [Papini, M.R., Pellegrini, S., 2006. Scaling relative incentive value in consummatory behavior. Learn. Motiv. 37, 357–378] and Pellegrini and Papini [Pellegrini, S., Papini, M.R., 2007. Scaling relative incentive value in anticipatory behavior. Learn. Motiv. 38, 128–154] showed that changes in the rat’s lever-pressing performance, runway running, and consumption of sucrose solutions after downshifts in incentive magnitude were a function of the ratio of postshift/preshift incentivemagnitudes. Here, two experiments using a Pavlovian autoshaping procedure studied the adjustment of pigeons and rats to changes in incentive magnitude. In Experiment 1, pigeons received light-food pairings, whereas in Experiment 2, rats received lever-sucrose pairings. As a result,key-pecking and lever-pressing developed in each experiment, respectively. Preshift incentivemagnitudes were downshifted so as to obtain postshift/preshift ratios of 0.125 and 0.25. Pigeons responded during the postshift phase according to the preshift incentive value and independently of the ratio value. However, rats showed ratio constancy, responding during the postshift in accordance with the postshift/preshift ratio, rather thanwith the absolutemagnitudes of either the preshift or postshift incentives. These results support the comparative hypothesis that the mechanisms underlying ratio constancy during incentive downshifts are unique to mammals.